Honami's Personality Aspects: A Study on Freud's Psychoanalysis of the Main Figures in Holy Mother's Novel by Akiyoshi Rikako - Sarjani, Andi Irma; Zuriyati, Zuriyati; Attas, Siti Gomo (JAPANEDU: Jurnal Pendidikan dan Pengajaran Bahasa Jepang, 2019)
This study aims to reveal the character of one of the main characters, Honami in the Holy Mother novel. The data source in this study is the Holy Mother novel wrote by Japanese author Akiyoshi Rikako,which has been published in Indonesia in 2016. The technique used for data collection in this study is library techniques. The method usedin conducting this research was the psychoanalysis method which was first put forward by Sigmund Freud. The results showed that based on psychoanalytic studies, the main character of the novel,a woman namedHonami, showed that the Id aspectinfluences all of herthoughts and actions. This was triggered by various events, namely herown misfortune which had many miscarriages and had a disease that made it difficult for herto get pregnant, and Kaoru's existence that changed herlife to became more meaningful. The emergence of fear and concern for her daughter because of the successive killings that struck a small child in the city where she lived, making her falsify and obscure the fact that Makoto, wascommitted murder to protect her daughter. The results also showed thatthe personality of the main character, Honami, is dominated by an element of the Egopersonality that defeats the Superego.